2013
DOI: 10.2527/jas.2012-5740
|View full text |Cite
|
Sign up to set email alerts
|

Individual physical characteristics of neonatal piglets affect preweaning survival of piglets born in a noncrated system1

Abstract: The aim of this study was to investigate the effects of individual physical characteristics on preweaning survival and growth of piglets born in a noncrate system. Data were collected from 3,402 neonatal piglets from 203 Landrace × Yorkshire sows housed in noncrate pens in a commercial Danish sow herd. Piglets were categorized into groups according to their survivability: surviving to weaning (SURV), stillborn (STILL), or dead between birth and weaning (DBW), which was subdivided into dead d 0 to 1 after farro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
126
1
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 115 publications
(131 citation statements)
references
References 50 publications
3
126
1
1
Order By: Relevance
“…Intrauterine growth retarded (IUGR) newborn piglet is born on time, and it is characterised by low birth body mass (below 1.1 kg), high perinatal mortality, and a “dolphin-like” head shape compared with “normal” piglets [1, 2]. The abnormality of head morphology is explained by prioritized brain development due to the “brain sparing effect” as part of a foetal adaptive reaction to placental insufficiency [3].…”
Section: Introductionmentioning
confidence: 99%
“…Intrauterine growth retarded (IUGR) newborn piglet is born on time, and it is characterised by low birth body mass (below 1.1 kg), high perinatal mortality, and a “dolphin-like” head shape compared with “normal” piglets [1, 2]. The abnormality of head morphology is explained by prioritized brain development due to the “brain sparing effect” as part of a foetal adaptive reaction to placental insufficiency [3].…”
Section: Introductionmentioning
confidence: 99%
“…Compared to loose-housing, these systems require also less space and are easier to manage, that is handling of animals and manure removal (Blackshaw et al, 1994;Barnett et al, 2001;Baxter et al, 2012;Hales et al, 2013). Nevertheless, crates are currently under discussion because the movement of the sows, and thus the natural animal behaviour and welfare are highly impaired (Lawrence et al, 1994;Jarvis et al, 1997).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the observation of higher body mass index values in low‐weight classes suggests L‐arginine's potential to modulate body mass index values in the pre‐natal period and improve the body mass index of low‐weight piglets. This is reflected in a higher pre‐weaning survival capacity (Hales, Moustsen, Nielsen, & Hansen, ).…”
Section: Discussionmentioning
confidence: 99%
“…The relationship between piglet body mass index and physiology remains unclear. Hales et al () assessed body mass index and other survival‐related variables and observed that piglets with a high body mass index could adequately nourish themselves and were not subjected to physiological challenges, such as hypothermia, and that the piglets that died on days 0 or 1 after birth had lower body mass indexes. These authors also observed that piglets with the same birthweight but different body mass index values differed in mortality risk.…”
Section: Discussionmentioning
confidence: 99%